Greener Reactions Under Solvent Free Conditions - Sapna (My University, 2009)
The toxicity and volatile nature of many organic solvents, particularly chlorinated hydrocarbons that are widely used in huge amounts for organic reactions have posed a serious threat to the environment. Thus, design of solventless catalytic reaction has received tremendous attention in recent times in the area of green synthesis. Five reactions viz., Reformatsky reaction, Luche reaction and reactions involving the synthesis of bis(β-naphthol), Schiff’s base, and a three component coupling reaction has been studied under solvent free conditions during the present investigation. Reformatsky reaction of benzaldehyde with ethyl bromoacetate give β-hydroxy ester under solventless conditions. This reaction involves the condensation of aldehydes with organozinc derivatives of α-halo esters to give β-hydroxy esters. Similarly synthesis of homoallylic alcohols by the Luche reaction has been carried out efficiently in the absence of solvent where benzaldehyde along with allyl bromide in presence of Zn-NH4 Cl and in the absence of solvent gave the Luche product. Solventless synthesis of bis(β-naphthol) involves the radical coupling reaction of β-naphthol in the presence of ferric chloride. Three component coupling reaction of benzaldehyde, ethyl acetoacetate and urea on heating at 90°C for one hour gave dihydropyrmidinones. Schiff base was also synthesized from aniline and benzaldehyde in an effort to study reactions under solvent free conditions.
M.Sc. (Chemistry)
Keywords: Solventless reactions; solid state reactions